Utilization of Tofu Dregs into Soy Sauce: Study of the Proportion of Tofu Dregs Filtrate With Coconut Sugar on Soy Sauce Quality - Andriani Eko Prihatiningrum; Belia Findurina (Universitas Muhammadiyah Sidoarjo, 2010)
The study aims to determine the effect of treatment the proportion of filtrate tofu with coconut sugar to quality soy tofu. The design used a randomized block design (RBD) consisting of six treatments with the proportion of pulp filtrate: coconut sugar is A (125 ml: 157.5 grams) , B (125 ml:172.5 grams), C (125 ml:187.5 grams), D (125 ml:202.5 grams), E (125 ml:217.5 grams), F (125 ml:232.5 grams) and repeated three times. The variables measured include chemical analysis (protein content, water content, sucrose concentration , pH), organoleptic test (flavor, aroma, color) and viscosity. The results showed: (i) the difference is very noticeable effect on protein content, sucrose concentration, pH, aroma, taste and viscosity , (ii) the difference was not significant on the moisture content and color and (iii) the best treatment is the proportion of the filtrate tofu with coconut sugar 125 ml: 232.5 grams of soy pulp that produces the protein content of 1.144 %, 2.109 % sucrose content, water content of 49.497 % , 6.630 % and the pH value organoleptic a taste panelists to 3,333 (regular), aroma 3,667 (love), color 3.467 (regular) and viscosity of 3.467 (normal).